HIV/AIDS-tuberculosis (pulmonary and extra pulmonary) co-infection: CD4 correlation - Siddeswari, R.; Amaravathi, K. S.; Rao, N. Srinivasa; ., Sanjeev; Rewari, B.; Kumar, Prabhu (International Journal of Research in Medical Sciences, 2016)
Background: AIDS is the leading cause of death among people 15-59 years old in low income countries. Worldwide, approximately one-third of all AIDS-related deaths are associated with TB. TB is the primary cause of death for 10-15% of patients with HIV infection. So the present study was conducted to find the correlation between sputum positivity and CD4 cell count in patients with HIV/AIDS-Tuberculosis co-infection. Methods: The present study was a retrospective hospital based study of patients with HIV/AIDS-Tuberculosis co-infection, attending ART centre, department of medicine, Osmania general hospital, Hyderabad, Telangana, India between November 2014 to September 2015. Data included clinical profile, complete blood picture, renal and liver function tests, sputum microscopy and C/S and chest X-Ray and others as and when required. Results: We included 180 HIV/AIDS infected patients on ART with tuberculosis (TB) co-infection. Out of 180 patients, 132 were males and 48 were females. Among male’s ≥40 (51.51%) year’s age group and among females 30-39 (56.25%) year’s age group was the most commonly affected. Out of 180 cases 60 were sputum positive. 60 sputum negative pulmonary tuberculosis and 60 were extra pulmonary TB. CD4 cell count was <200/mm3 in 36 (60%) of sputum positive TB, 43 (71.7%) of sputum negative pulmonary TB & 39 (65%) of extra pulmonary TB patients. CD4 cell count was 200-400/mm3 in 16(26.7%) of sputum positive pulmonary TB, 13 (21.7%) of sputum negative TB and 19 (31.7%) of extra pulmonary TB patients. CD4 cell count was >400/mm3 in 8 (13.3%) of sputum positive pulmonary TB, 4 (6.6%) of sputum negative pulmonary TB and 2 (3.3%) of extra pulmonary TB patients. Conclusions: Present study concludes that male sex and age group >30 years were the commonly affected population. All forms of tuberculosis were common when CD4 count was <200 cells/mm3. The sputum negativity was higher with lower CD4 counts.